(untitled) (Journal of Parents and Teachers, 2013)
From a current practice analysis, the author of this article criticizes students of secondary education that simply repeat ideas from texts. She tries to guide the teacher, who should be the one that tries to avoid this situation, offering a teaching guide with a series of key questions.